Strategi Humas Melalui Program Serap Aspirasi Dan Safari Kreatifitas Siswi Di Smk El Mosthofa Untuk Meningkatkan Marketing Pendidikan - Madani, Jalaluddin; Rakandana, Ipung; Mansur, Mansur (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Education is an institution in charge of delivering students to become quality human beings. To go to the people who qualified then of course must first educational institutions must also be qualified, then one of them must establish a good relationship to the community. Because education is not only focused on teachers and students, but also the community must be involved in it. Society also has a great influence on the progress and sustainability of educational institutions, and educational institutions also have to establish good relations with the community, so it is known by the term Public Relations (HUMAS) or Public Relations (PR). And it makes it easier for educational institutions to communicate to the community.